Proceedings of the 24th ACM International on Conference on Information and Knowledge Management 2015
DOI: 10.1145/2806416.2806476
|View full text |Cite
|
Sign up to set email alerts
|

Searching and Stopping

Abstract: Searching naturally involves stopping points, both at a query level (how far down the ranked list should I go?) and at a session level (how many queries should I issue?). Understanding when searchers stop has been of much interest to the community because it is fundamental to how we evaluate search behaviour and performance. Research has shown that searchers find it di cult to formalise stopping criteria, and typically resort to their intuition of what is "good enough". While various heuristics and stopping cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 36 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…Overall, their resident time was close to the optimal resident time, although they tended to overstay, corresponding to the findings from previous studies (e.g., Hutchinson et al, 2008). In regard to the strategies used by the participants, most participants relied on the GUT strategy, while a minority was best described by the FT strategy, which, again, is in line with previous research (Hutchinson et al, 2008;Maxwell et al, 2015;Wilke et al, 2009). This suggests that separating the decision process from processing rewards did not change participants' strategies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, their resident time was close to the optimal resident time, although they tended to overstay, corresponding to the findings from previous studies (e.g., Hutchinson et al, 2008). In regard to the strategies used by the participants, most participants relied on the GUT strategy, while a minority was best described by the FT strategy, which, again, is in line with previous research (Hutchinson et al, 2008;Maxwell et al, 2015;Wilke et al, 2009). This suggests that separating the decision process from processing rewards did not change participants' strategies.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, while it was not our intention, the design of Experiment 2 was also the best for pushing participants to use the FT over the GUT strategy. The preference for using the GUT strategy over the other strategies matches findings from previous studies (Hutchinson et al., 2008; Maxwell et al., 2015; Wilke et al., 2009), suggesting that although people are able to adjust their foraging strategy to the environment, that is, by staying longer when travel time between patches increases, they do not switch strategies. This deviates from research in other areas of decision‐making reporting that people adaptively switch between different strategies (Gigerenzer & Selten, 2002; Kolling & Akam, 2017; Payne et al., 1988).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…how many items look relevant?). His poster compared different stopping strategies based on fixed and adaptive rules [17,18]. Experiments conducted on a large news collection for the task of ad-hoc topic search revealed that adaptive stopping strategies were more robust and lead to greater retrieval performance.…”
Section: An Initial Investigation Into Fixed and Adaptive Stopping Stmentioning
confidence: 99%
“…Traditional simulation methods typically decompose a user's interactive search behavior into a series of independent steps, including submitting queries, browsing Search Engine Results Pages (SERPs), clicking results, reading and evaluating documents, and deciding when to stop [3]. Therefore, they require a dedicated simulation strategy to be designed for each step, such as generating search queries by extracting terms from language models associated with specific documents or topics [1,2,4,7,17], estimating the probability of a user clicking on search results based on historical data using click models [5,8,11,12,16], and deciding when a user stops searching based on a set of predefined simplistic assumptions through heuristic rules [10,19,[24][25][26]. However, these approaches fail to fully consider the dynamic and interdependent nature of user behavior, In particular, they often fail to model how some cognitive factors, such as the information needs and background knowledge, and cognitive processes, including the learning and reasoning, would affect and drive user's action.…”
Section: Introductionmentioning
confidence: 99%